Prospective study on ultrasonographic measurement of the spinal canal depth in very low birth weight infants - Mohammad A A Bayoumi; Mohammed Abdul Khader Gaffari; Ashraf Gad; Jihad Al-Shouli; Aishat Akomolafe; Loay Alkamel; Ahmad Albaridi; Alaa Elfakharany (BMJ Paediatrics Open)
Background Lumbar punctures (LP) in very low birth weight (VLBW) infants often have low success rates. Point-of-care ultrasound (POCUS)-based spinal canal depth (SCD) measurements may provide better outcomes.Aim To provide POCUS-based SCD measurement values for VLBW infants using different calculation methods at the L4/5 and L3/4 levels.Methods This prospective observational study involved 31 VLBW infants in the neonatal intensive care unit at Women’s Wellness and Research Center, Doha, Qatar, from March 2022 to September 2023. The outcome measures included anterior (ASCD), mid (MSCD) and posterior spinal canal depth (PSCD) measurements. The study compared results from different calculation methods at the L4/5 and L3/4 levels.Results A total of 63 ultrasound examinations were performed on 31 infants. The median gestational age was 25.0 weeks (IQR 24–27), with a birth weight of 817.9±170.2 g and a birth height of 31.6±2.8 cm. The MSCD at L4/5 was 7.1±0.5 mm and 6.9±0.5 mm at L3/4, with a mean difference (MD) of 0.20 (95% CI 0.15 to 0.24; p<0.001). The mean SC anteroposterior diameter at L4/5 was 3.8 mm versus 4.2 mm at L3/4 (MD −0.334, 95% CI −0.45 to 0.22; p<0.001). Weight-based and body surface area (BSA) calculations correlated best with MSCD at both levels. The MSCD in millimetres was determined by the equations 2×weight (kg)+6 (R²=0.71) at L4/5 and (R²=0.70) at L3/4 and 25×BSA (m²)+5 (R²=0.71) at L4/5 and (R²=0.73) at L3/4 levels. Moreover, body weight and BSA showed a slightly stronger correlation with ASCD measurements compared with PSCD. All SCD measurements demonstrated a poor linear correlation with body length (cm) and body mass index (kg/m²).Conclusion This study offers reference data for POCUS-based SCD measurements in VLBW infants, demonstrating that body weight and BSA effectively predict SCD. These findings could enhance the accuracy of LPs in this population when ultrasound guidance is unavailable, supporting personalised care.